Pricing of electricity swaps with geometric averaging - Annika Kemper; Maren Diane Schmeck (Bielefeld University, Center for Mathematical Economics (IMW), 2023)
In this paper, we provide empirical evidence on the market price of risk for delivery periods (MPDP) of electricity swap contracts. As introduced by Kemper et al. (2022), the MPDP arises through the use of geometric averaging while pricing electricity swaps in a geometric framework. In preparation for empirical investigations, we adjust the work by Kemper et al. (2022) in two directions: First, we examine a Merton type model taking jumps into account. Second, we transfer the model to the physical measure by implementing mean-reverting behavior. We compare swap prices resulting from the classical arithmetic (approximated) average to the geometric weighted average. Under the physical measure, we discover a decomposition of the swap's market price of risk into the classical one and the MPDP. In our empirical study, we analyze two types of models, characterized either by seasonality in the delivery period or by a term-structure effect, and identify the resulting MPDP in both cases.
urn:nbn:de:0070-pub-29781549
Keywords: G13; Q40; 330; Electricity Swaps; Delivery Period; MPDP for Diffusion and Jump Risk; Mean-Reversion; Jumps; Samuelson Effect; Seasonality